Differential effects of synbiotic delivery route (Feed, water, combined) in broilers challenged with Salmonella Infantis - Victoria Drauch; Mahdi Ghanbari; Nicole Reisinger; Michaela Mohnl; Claudia Hess; Michael Hess (Poultry Science, 2025)
Salmonella enterica subsp. enterica serovar Infantis (S. Infantis) presents a persistent and multi-drug-resistant threat to poultry production, highlighting the need for effective control strategies. This study evaluated the impact of a S. Infantis infection in broiler chickens across various parameters, including organ colonization, gut microbiota, and immune function. We also assessed the mitigation potential of a synbiotic, multispecies feed additive, administered via three routes applicable for the field: feed only, drinking water only, and a combination of both. Our results demonstrated that the combined administration route yielded notably positive effects on several parameters, followed by the drinking-water only administration. This approach resulted in significant improvements in gut microbiota health, characterized by increased levels of beneficial microbes such as Lactobacillus, Ligilactobacillus, and Butyricicoccus, and a decrease in potentially harmful genera from the Proteobacteria phylum. Reduction of S. Infantis load was observed in caecum, ileum, and spleen over time albeit shedding was not influenced. The drinking water-only administration showed a significant reduction of S. Infantis colonization in the caecum on the last sampling day. Immune response analysis indicated no significant differences in serum antibody levels between control and treatment groups. These findings underscore the impact of both combined and drinking water-only synbiotic, multispecies feed additive administration on the gut microbiota and a possible route for reducing S. Infantis in poultry production. The obtained data provide valuable guidance for optimizing synbiotic use in commercial poultry management, enabling enhanced pathogen control and improved gut health.